The therapeutic effects of saikosaponins on depression through the modulation of neuroplasticity: From molecular mechanisms to potential clinical applications - Shen Chen; Ke Wang; Hongzhan Wang; Yang Gao; Kexin Nie; Xinyue Jiang; Hao Su; Yueheng Tang; Fuer Lu; Hui Dong; Zhi Wang (Elsevier, 2024)
Depression is a major global health issue that urgently requires innovative and precise treatment options. In this context, saikosaponin has emerged as a promising candidate, offering a variety of therapeutic benefits that may be effective in combating depression. This review delves into the multifaceted potential of saikosaponins in alleviating depressive symptoms. We summarized the effects of saikosaponins on structural and functional neuroplasticity, elaborated the regulatory mechanism of saikosaponins in modulating key factors that affect neuroplasticity, such as inflammation, the hypothalamic-pituitary-adrenal (HPA) axis, oxidative stress, and the brain-gut axis. Moreover, this paper highlights existing gaps in current researches and outlines directions for future studies. A detailed plan is provided for the future clinical application of saikosaponins, advocating for more targeted researches to speed up its transition from preclinical trials to clinical practice.